PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL MASYARAKAT BALI - I Wayan Sapta Wigunadika (Purwadita : Jurnal Agama dan Budaya, 2018)
Adoption of technology has brought many problems in social life. But the need for technologycan not be postponed because its function as a plane that facilitates the handling ofhuman affairs more difficult to abandon. As a result a variety of access appears. The ease thattechnology offers has an effect on the user’s mentality. Technological users are not only happyto take quick (instant) ways, but also often fall into thoughts that degrade the values of humanityitself. The neglect of human values is not only practical, but it is found in academic life.Let’s look at a moment of education in Japan which is considered a model of the country that isable to reach modernization rapidly and creatively but still maintain strong tradition and thevalues contained in it. They are a nation that is rooted in the traditions (cultural up root).Japanese tradition is experiencing various changes but the Japanese spirit does not fade in it. Ifthe Indonesian people want to follow the example of Japan, education in Indonesia is the time tomove from practice education and do not expect to catch up from other countries if educationproblems have not been addressed. When there is an international school discourse, we shouldfavor local wisdom to gain international recognition, instead of importing foreign cultures.Local wisdom of Balinese people is very important to be studied and applied in the life ofsociety. Therefore, the noble values that exist in Balinese culture are appropriate in adaptationand integrated in the implementation of education, both formal and non-formal education. Moreoverformal education, local wisdom is very well adapted and integrated in learning. localwisdom from Bali is very important and well included in formal education at all levels of education.Keywords: Character Education, Based, Local Wisdom